Review of Efficient Routing In Delay Tolerant Network (International Journal of Engineering and Computer Science, 2015)
Delay Tolerant Networking (DTN)[2][3] has been proposed as a potential solution for this technical challenge as it is designed to offer a solution for routing in a network which is not always connected.  Ad-hoc network[6] is a decentralized type of wireless network. There is no pre existing infrastructure, like the base station to coordinate the flow of messages between the nodes. To deliver a message to a node, the shortest path to the destination node is computed. Ad hoc networks can use flooding for forwarding the data. Ad hoc routing assumes that there is an end to end connectivity between the nodes. However this not the case for DTNs. DTNs or the Delay Tolerant Networks are ad hoc networks in which contacts are not available at all times. The messages are buffered till the contacts are available and are then forwarded on the contacts when available. In this paper, we evaluate some of the most prominent routing protocols for Delay-Tolerant Networks such as Epidemic[1], PRoPHET , Contact Graph Routing and Dynamic social grouping (DSG)